Justifying by degrees: A grounded theory of men's decision‐making process in infidelity. - Perez, Carlos; Fife, Stephen T.; Eggleston, Dane; Whiting, Jason B. (Journal of Marital & Family Therapy, 2023)
Infidelity is a common reason couples seek therapeutic help as betrayed partners are often hurt and dismayed by their partners' decision to engage in an extradyadic relationship. Despite its common occurrence, there are very few empirical studies of the decision‐making process behind infidelity. To address this gap, the current study used grounded theory, a qualitative approach commonly used to develop theories from participants' experiences, to explore men's processes in deciding to engage in infidelity. Analysis of interviews with participants (n = 13) resulted in a grounded theory of decision‐making by cisgender men who participated in infidelity while in a committed, heterosexual relationship. The results suggest that the decision involves a continuous process of justification and rationalization. Major categories of the theory include the preaffair context, snowballing, motivated reasoning, and postaffair decisions. Clinical implications are also included.